2014
DOI: 10.1111/ajt.12690
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Retransplant Kidney Recipients: Relisting and Outcomes From Patients’ Primary Transplant

Abstract: As of November 2013, 14.5% of the waitlist for a donor kidney comprised patients awaiting a retransplant. We performed a retrospective cohort study of 11 698 adult solitary kidney recipients using national Scientific Registry of Transplant Recipients data transplanted between 2002 and 2011. The aim was to investigate whether outcomes from patients' initial transplants are significant risk factors for patients' repeat transplants or for likelihood of relisting after a failed primary transplant. Retransplant rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 11 publications
(27 reference statements)
2
44
1
2
Order By: Relevance
“…15 Incorporating prior transplant outcome data to retransplant outcomes is a critical issue to be highlighted. In a study published in 2014, 16 retransplant recipients were more likely to be treated for acute rejection (P = .005) or were hospitalized (P = .001) within 1 year of retransplant if these outcomes were experienced within 1 year of primary transplant. Delayed graft function after primary transplants was associated with 35% increased likelihood of recurrence (P < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Incorporating prior transplant outcome data to retransplant outcomes is a critical issue to be highlighted. In a study published in 2014, 16 retransplant recipients were more likely to be treated for acute rejection (P = .005) or were hospitalized (P = .001) within 1 year of retransplant if these outcomes were experienced within 1 year of primary transplant. Delayed graft function after primary transplants was associated with 35% increased likelihood of recurrence (P < .001).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to determine the effects of failed allograft nephrectomy on subsequent transplants and the importance in sensitization. 1 The rate of renal retransplant has increased from 7.1% for living donors and from 9.7% in deceased donors in 2007 2 to 11.8% in 2011, 3 to 14.5% in 2014, 4 and to 15% in 2015, 5 with immunologic risk much greater among retransplanted patients than first-time kidney recipients. It is likely that retrans plant will become even more prevalent in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of resumption of graft function does not affect long-term survival as much as a delay in function. 8 In a retrospective study of graft survival that excluded patient deaths (n = 472 transplant recipients), Hellegering and associates 23 reported that the difference in death-censored survival rates between patients with DGF and normal graft function resulted in an adjusted hazard ratio of 6 24 Understanding the reason for the persistently close relation between graft survival and DGF warrants further study and a need to formulate further modalities for the optimal treatment of DGF after transplant.…”
Section: Effects Of Delayed Graft Function On Outcomes Of Living-donomentioning
confidence: 99%
“…Непосредственные и отдаленные результаты ретрансплантаций опре-деляются рядом факторов, связанных с основным заболеванием, длительностью функционирования и причиной утраты первого трансплантата [4], типом и качеством донорского органа [5,6], иммунологи-ческим статусом пациента [7], а также наличием у него сопутствующих заболеваний [8].…”
Section: Introductionunclassified